Efficiency of spraying with spirulina and variety on the growth of bean plant under drip irrigation system - Intesar Kareem Abdulhassan (Wasit Journal for Pure Sciences)
The utilization of bio-stimulants in agricultural settings has emerged as a potentially fruitful technique for enhancing the development and production of crops. Microalgae extracts are a form of bio-stimulant that has recently garnered much attention. These extracts are well-known for their high metabolic activity, bioactive chemicals, and capacity to boost plant growth and development.  The experiment aimed to determine the efficiency of Spirulina platensis extracts by foliar spraying on bean plants. The experiments were carried out in the autumn of 2023   in  Diyala Governorate to study the efficiency of spraying with spirulina extract and its physiological effect on bean plant growth. The experiment was carried out in RCBD  design with three replications,   using four concentrations of spirulina  (0, 0.25, 0.50, and 1.0) %  and two varieties of bean plants   (  Barcelona and luz de otono). The results showed a superiority concentration of 1.0%    in all studied traits. Which record in 73.28  cm,51,43 SPAD,1.41,42.03 g/ plant,3.90%,0.156%, and 1.41%    for the high plant, chlorophyll index, leaf area index, dry matter, N%, P%, and K% respectively,   Barcelona variety superiority in all characteristics except leaf area index (LAI). The results also showed that the binary interaction between spray and variety significantly affected the studied factors.